Campus life services system (instructor and participant module) in UiTM Shah Alam / Salfina Amirudin - Amirudin, Salfina (2014)
Student in the UiTM lack of involvement in the community services and there is no channel for them to involve themselves. As for the staffs, they lack of time to find the non-academic lesson mostly for their children or themselves. Campus Life Services was developed to help the student to take part in the community services using the skills they have or learned while in the UiTM. To develop this system, the author use Agile methodology as the method because using this method, the author can change the flow of the system to meet the requirement. This system will be implement in the UiTM as it will attract the staff and the student to take part in this community services. It also can help the student to sharpen soft skills such as communication skills. As for staff, it will reduce the time management in searching of the non-academic lesson.